2021
DOI: 10.1111/poms.13459
|View full text |Cite
|
Sign up to set email alerts
|

Designing Digital Rollovers: Managing Perceived Obsolescence through Release Times

Abstract: When releasing a new version of a durable product, a firm aims to attract new customers as well as persuade its existing customer base to upgrade. This is commonly achieved through a rollover strategy, which comprises the price of the new product as well as the decision to discontinue the sale of the existing product (solo rollover) or to sell the existing product at a discounted price (dual rollover). In this study, we argue that the timing of the new product release is an important—but commonly overlooked—th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Li and Graves (2012) and Koca et al (2010) consider both the pricing and inventory replenishment decisions concurrently. Liang et al (2014), Liu et al (2018) and Koca et al (2021) propose pricing policies for the firm incorporating how strategic customers react to the rollover under varying levels of innovation. Chau and Desiraju (2017) study rollover strategies in the context of network effects.…”
Section: Related Literaturementioning
confidence: 99%
“…Li and Graves (2012) and Koca et al (2010) consider both the pricing and inventory replenishment decisions concurrently. Liang et al (2014), Liu et al (2018) and Koca et al (2021) propose pricing policies for the firm incorporating how strategic customers react to the rollover under varying levels of innovation. Chau and Desiraju (2017) study rollover strategies in the context of network effects.…”
Section: Related Literaturementioning
confidence: 99%
“…Arslan et al [3] also investigated the timing of new product introduction by a firm and the pricing decision for multiple product generations. Koca et al [24] investigated the introduction of a new version of a digital product that attracts new customers and entice existing customers to upgrade and showed that the choice of the release timing of the new product can induce a sufficiently large portion of the existing customers to upgrade and hence lead single rollover to become the optimal strategy. When introducing a new product, manufacturers may implement trade-in programs to incentivize existing customers to buy the new product.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to whether the last generation of product should be phased out as soon as the new generation is launched, the product rollover strategy can be classified as single product rollover or dual product rollover. There is a stream literature that studies whether a single or dual rollover strategy should be adopted when considering various factors such as the cannibalization effect (Ferguson & Koenigsberg, 2007), product introduction and phase‐out times (Koca et al, 2021; Lim & Tang, 2006), and the strategic behavior of customers (Levinthal & Purohit, 1989; Liang et al, 2014). Some other papers focus on specific operational issues in the presence of product rollover on the basis of a given rollover strategy.…”
Section: Introductionmentioning
confidence: 99%